Serial Polygamy without the Consent of Legal Spouses: Juridical Analysis and Study of Islamic Family Law - Khairina Wati; Edi Darmawijaya; Aulil Amri (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
This study analyzes the practice of unregistered polygamous marriages (poligami siri) conducted without the knowledge of the lawful wife, which remains prevalent in Gampong Barueh, Kota Jantho, Aceh Besar. This phenomenon reveals a disparity between legal regulations and social practices, as it contravenes Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law, both of which require the consent of the first wife and official marriage registration. The research employs a juridico-empirical approach through case and conceptual studies, involving interviews with the village head (Keuchik) as the key informant and two respondents consisting of a married couple. The findings indicate that poligami siri is often conducted secretly, motivated by economic factors and biological needs. From the perspective of Islamic jurisprudence (fiqh), such marriages are deemed valid as they fulfill the essential elements (arkan) of marriage; however, from a legal standpoint, they lack state recognition, resulting in legal uncertainty, gender discrimination, and child neglect. The practice disregards the Islamic principles of justice (al-‘adl) and responsibility (mas’uliyyah). The study recommends strengthening the supervisory roles of the Office of Religious Affairs (KUA) and the Sharia Court (Mahkamah Syar’iyah), implementing collective isbat nikah programs, and enhancing family law literacy through community legal education. It further concludes that greater synergy between Islamic law and national law is essential to ensure that polygamous marriages are not only religiously valid but also legally enforceable to protect the rights of wives and children.